2011
DOI: 10.1158/1078-0432.ccr-10-1689
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90-Sheltered Overexpression of Insulin-Like Growth Factor 1 Receptor Contributes to Malignancy of Thymic Epithelial Tumors

Abstract: Purpose: The underlying molecular mechanisms of thymic epithelial malignancies (TEMs) are poorly understood. Consequently, there is a lack of efficacious targeted therapies and patient prognosis remains dismal, particularly for advanced TEMs. We sought to investigate protumorigenic mechanism relevant to this understudied cancer.Experimental Design: Recently established cell lines derived from thymic epithelial tumors were used as a model system. The antitumor activity of specific heat shock protein 90 (Hsp90) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
(58 reference statements)
2
17
0
Order By: Relevance
“…In addition, the present study indicated that high cERβ5 expression in thymic tumors was correlated with longer OS and PFS, which was in accordance with previous results (18,20,21,23,28,29). However, the fact that cERβ5 was overexpressed in thymic tumors, while having an inhibiting biological effect, suggested that cERβ5 may be involved in other functions of the thymic tumor development and progression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the present study indicated that high cERβ5 expression in thymic tumors was correlated with longer OS and PFS, which was in accordance with previous results (18,20,21,23,28,29). However, the fact that cERβ5 was overexpressed in thymic tumors, while having an inhibiting biological effect, suggested that cERβ5 may be involved in other functions of the thymic tumor development and progression.…”
Section: Discussionsupporting
confidence: 92%
“…Exposure to sex steroid hormones, for instance during estrogen therapy, results in thymic atrophy and loss of cellularity in animals (18,20,21). Thymic atrophy induced by estrogens contributes towards certain complicated and unclear mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in other cancer types [83,[124][125][126], PU-H71 also potentiated G 2 /M arrest, and depleted Hsp90 client proteins AKT, pERK, RAF-1, c-MYC, c-KIT, IGF1R, hTERT (human telomerase reverse transcriptase) and EWS-FLI1 (Ewing's sarcoma-Friend leukemia integration 1 transcription factor). In regards to potential drug synergy with bortezomib, Fa-CI (fraction affected-combination index) plots and isobolographic analyses confirmed synergism between PU-H71 and bortezomib.…”
Section: Ewing's Sarcomasupporting
confidence: 54%
“…IGF-1R protein overexpression has also been observed in thymic carcinoma, being present in 6 of 7 thymic carcinomas in a study by Girard et al [16]. Using thymic carcinoma cell lines these results were confirmed by Breinig et al [37]. In addition, the authors were able to demonstrate that heat shock protein 90 (Hsp90) inhibition was associated with antitumor activity by blocking multiple cancer-relevant signaling pathways, including the IGF-1R pathway.…”
Section: Oncogenesmentioning
confidence: 80%